2022
DOI: 10.1097/txd.0000000000001420
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Imaging for Viability Assessment of Human Liver Allografts During Normothermic Machine Perfusion

Abstract: L iver transplantation (LT) is the only curative therapy for patients with end-stage liver disease. In recent decades, LT is characterized by an increasing waiting list mortality due to the lack of donor organs. 1 The utilization of extended criteria donor (ECD) organs has become frequent in order to overcome the severity of organ scarcity. 2 As ECD organs may be associated with an inferior outcome of LT, risk-minimizing strategies are sought after. 3 Normothermic machine perfusion (NMP) is a revived preservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Other groups recommend adjusting flow to account for liver volume, requiring 0.1 ml/min/g for hepatic artery and 0.33 ml/min/g for portal vein flows [22]. There are several techniques currently under investigation that may more accurately measure liver perfusion, including hyperspectral imaging and indocyanine green (ICG) clearance; however, none are routinely used in clinical practice [27,28].…”
Section: Viability Assessmentmentioning
confidence: 99%
“…Other groups recommend adjusting flow to account for liver volume, requiring 0.1 ml/min/g for hepatic artery and 0.33 ml/min/g for portal vein flows [22]. There are several techniques currently under investigation that may more accurately measure liver perfusion, including hyperspectral imaging and indocyanine green (ICG) clearance; however, none are routinely used in clinical practice [27,28].…”
Section: Viability Assessmentmentioning
confidence: 99%
“…A significantly higher THI was seen in discarded livers compared with transplanted livers end NMP. Kneifel et al also used HIS during NMP at 1, 2 and 4 h of perfusion and showed that StO 2 and THI predicted lactate values at 1 and 2 h of NMP, THI also predicted lactate values at 4 h [55 ▪ ]. Lau et al [56 ▪▪ ] analyzed the indocyanine green (ICG) plasma-disappearance-rate (PDR) and the ICG-perfusion with a near-infrared camera during 7 days of NMP.…”
Section: Promising Viability Criteriamentioning
confidence: 99%
“…66,67 Hyperspectral imaging represents a novel technology of increasing interest for monitoring organ microcirculation, functional biomarkers, water, hemoglobin, or tissue oxygenation. [68][69][70][71] Finally, nontoxic fluorescent dyes offer a means to visualize vasculature and organ function; for example, indocyanine green applied in liver NMP supports the real-time visualization of the intrahepatic biliary tree. 72 Using sensors in direct contact with the organ in question represents another attractive monitoring prospect; for example, implantable oxygen biosensors can monitor tissue oxygen tension, 73 whereas laser-Doppler technology can analyze organ microcirculation.…”
Section: Design Of An Nmp System and Organ Assessmentmentioning
confidence: 99%
“…The administration of therapies through the perfusate has several benefits that make NMP an attractive therapeutic option, including more efficient delivery, lower doses, and reduced unwanted side effects in nontarget organs. 174 The immunomodulatory properties of mesenchymal stem cells 57–159 and multipotent adult progenitor cells 160–162 have shown beneficial effects during liver, lung, and kidney NMP, presumably due to their immunomodulatory properties, which prompt both anti-inflammatory and regenerative responses. 157,160–162 In human models, initially discarded kidneys 160 and livers 161 treated with multipotent adult progenitor cells or preterm-neonate progenitor cells 162 exhibited improved viability, even meeting established criteria.…”
Section: Remaining Challenges and The Future Of Nmp Systemsmentioning
confidence: 99%